RETRACTED ARTICLE: Parameter estimation of the multivariate unrestricted skew-normal distribution using ECM algorithm - Contreras-Reyes, Javier E.; Maleki, Mohsen (Communications in statistics. Simulation and computation, 2025)
We, the Editor and Publisher of Statistics, have retracted the following article: Javier E. Contreras-Reyes & Mohsen Maleki. Parameter estimation of the multivariate unrestricted skew-normal distribution using ECM algorithm. Communications in Statistics - Simulation and Computation. Latest Articles. 2023. https://doi.org/10.1080/03610918.2023.2289360 Following publication, the Publisher identified concerns regarding the peer review process for this article. An investigation by the Taylor & Francis Publishing Ethics & Integrity team in full cooperation with the Editor-in-Chief concluded that the article was not peer-reviewed appropriately, in line with the Journal's peer review standards and policy as one of the co-authors of the article was found to have acted as a reviewer. As the stringency of the peer review process is core to the integrity of the publication process, the Editor-in-Chief and Publisher have decided to retract the article. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".